![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
23.27.24=23+7+4=214
23.24:25=23+4-5=27
(-3)+(-125)+(-25)
=-128+(-25)
=-153
25+(-38)=25-38=-13
126+159=285
120+(-135)+200
=120-135+200
=-15+200
=185
2^3x2^7=2^10x2^4=2^14=16384
2^3x2^4=2^7:2^5=2^2=4
1300-(150.2+(900+90):9)=1300-(150.2+990:9)=1300-(300+11)=1300-311=989
(-3) + (-125)+(-25)= -(3+125+25)= -153
25 + (-38)= -(38-25)= - 13
(126)+159=285
(120)+(-135)+200= -(135-120) + 200= (-15) + 200= +(200-15)=185
![](https://rs.olm.vn/images/avt/0.png?1311)
a,-2x -(x-17)=34-(-x+25)
-2x-x+17=34+x-25
-3x+17=9+x
-3x-x=9-17
-4x=-8
-->4x=8
x=8:4
x=2
Vậy x=2
b,17-(16x-37)=2x+43
17-16x+37=2x+43
20-16x=2x+43
-16x-2x=43-20
-18x=23
x=23:(-18)
x=23/-18
Mà x là số nguyên nên --> x thuộc tập rỗng
c,-2x-3.(x-17)=34-2(-x+25)
-2x-3x+51=34-2.(-x)-25
-5x+51=9-(-2).x
-5x+(-2).x=9-51
-7x=-42
7x=42
x=42:7
x=6
Vậy x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =17-43=-26
b: =-34+34+11-11+105=105
c: \(=64+125\cdot100=12564\)
d: \(=60+\left[7^3-343\right]\cdot2017^{2018}=60\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (125 - x) + 25 = 98
125 - x = 98 - 25
125 - x = 73
x = 125 - 73
x = 52
b) 100 : (x + 20) = 68 : 34
100 : (x + 20) = 2
x + 20 = 100 : 2
x + 20 = 50
x = 50 - 20
x = 30
c) (3x + 12) . 5 = 25 . 4 - 10
(3x + 12) . 5 = 100 - 10
(3x + 12) . 5 = 90
3x + 12 = 90 : 5
3x + 12 = 18
3x = 18 - 12
3x = 6
x = 6 : 2
x = 3
d) 210 : (2x - 3) - 20 = 10
210 : (2x - 3) = 10 + 20
210 : (2x - 3) = 30
2x - 3 = 210 : 30
2x - 3 = 70
2x = 70 + 3
2x = 73
x = 73/2
a, ( 125 - x ) + 25 = 98
⇒ 125 - x = 73
⇒ x = 52.
Vậy..
b, 100 : ( x + 20 ) = 68 : 34
⇒ 100 : ( x + 20 ) = 2
⇒ x + 20 = 50
⇒ x = 30
Vậy...
c, ( 3 . x + 12 ) . 5 = 25 . 4 - 10
⇒ ( 3 . x + 12 ) . 5 = 90
⇒ 3 .x + 12 = 18
⇒ 3x = 6
⇒ x = 2.
Vậy...
d, 210 : ( 2 .x - 3 ) - 20 = 10
⇒ ( 2 .x - 3 ) - 20 = 21
⇒ 2x - 3 = 41
⇒ 2x = 44
⇒ x = 22.
Vậy..
a) (x+4x).25=125
=> 5x = 5
=> x = 1
b) 2(x+3) + 3(x+1) = 34
=> 2x+6+3x+3 = 34
=> 5x+9=34
=> 5x=25
=> x =5
\(\left(x+4x\right).25=125\\ 5x.25=125\\ 5x=125:25\\ 5x=5\\ x=5:5\\ x=1\\ 2\left(x+3\right)+3\left(x+1\right)=34\\ 2x+6+3x+3=34\\ 5x+9=34\\ 5x=34-9\\ 5x=25\\ x=25:5\\ x=5.\)